A Cross Sectional Survey on Evaluation of Oral Health Status, Prosthetic Need, and Quality of Existing Dental Prosthesis among Rural Population of Nadiad Taluka, Kheda District - Dr. Meena J. Shah; Dr. Somil Mathur; Dr. Vilas Patel; Dr. Aayush J. Shah (The Bioscan, 2024)
Aim: This study aims to evaluate the oral health status, prosthetic needs, and the quality of existing dental prostheses among the adult rural population of Nadiad Taluka, Gujarat, India, to provide insights for improving oral health services in this region. Methodology: A cross-sectional descriptive study was conducted with a sample of 500 adult participants from Nadiad Taluka, selected using a 95% confidence interval and a ±5% margin of error. Data were collected through surveys conducted across outpatient departments, including N. D. Desai Medical College, Mahagujarat Medical Society, and Santram Mandir Hospital. The study assessed oral health conditions, prosthetic needs, and the quality of existing prostheses. Statistical analysis was performed with a significance threshold of p < 0.05. Results: The study revealed high prevalence rates of dental caries (64%) and periodontal disease (56%). Complete edentulism was observed in 10% of participants, while 40% had partial edentulism. The demand for prosthetic interventions was substantial, with 60% requiring some form of prosthetic treatment. The quality of existing dental prostheses varied significantly, with only 20% reporting good fit and comfort, and 60% indicating no maintenance of their prostheses. Educational and income levels were significantly associated with oral health outcomes and prosthetic needs. Conclusion: The findings highlight the critical need for targeted oral health interventions in Nadiad Taluka. To address the high prevalence of oral diseases and inadequate prosthetic services, it is essential to enhance oral health education, improve access to affordable dental care, establish regular maintenance programs, and provide socio-economic support. Implementing these recommendations could significantly improve oral health outcomes and the quality of life for the rural population of Nadiad Taluka.